Optical meta-waveguides for integrated photonics and beyond - Yuan Meng (Nature Publishing Group, 2021)
Recent years have witnessed substantial potential in allying meta-optics with diverse waveguide platforms to enable exotic manipulation of guided light signals. This review cataloged recent advances on meta-waveguides for photonic integration.